The Genesis and Development of Dewey S Pedagogy in Chile - Caiceo-Escudero, J (FAHRENHOUSE, 2016)
On the occasion of the 100th anniversary of the publication of John Dewey s Democracy and Education, we analyse the impact of this seminal work on the history of education in Chile. We review and describe his influence on both secular and Catholic spheres in the country at the beginning of the 20th century, and the major milestones in the educational reforms implemented according to his theories. This historical study relies on both primary and secondary sources, and features a documentary analysis of the works influenced by his ideas. It forms part of a series of investigations on the topic carried out by the author over the last thirty years.